Vitamin E supplementation does not alter physiological performance at fixed blood lactate concentrations in trained runners - Cobley, J. N.; Marrin, K. (The Journal of Sports Medicine and Physical Fitness, 2012)
AIM:The aim of the study was to determine the direction of change in performance variables at fixed blood lactate concentrations following vitamin E (VE) supplementation. METHODS:In a paired-matched design twelve (male: N.=8; female: N.=4) trained runners were allocated to a VE (N.=6; 268 mg/d) or placebo (N.=6; glucose: 30 mg/d) group for 35 days. Participants completed a discontinuous incremental exercise test, pre and post supplementation, to determine peak oxygen uptake (VO2peak) running velocity and percentage of peak oxygen uptake (%(VO2peak) at the lactate threshold (TLAC) and the onset of blood lactate accumulation (OBLA). Participants maintained a standardised training regime throughout the supplementation period. RESULTS: VE supplementation failed to significantly enhance velocity at TLAC (P=0.91) and OBLA (P=0.22) compared to a placebo treatment. Analogously, VE did not significantly enhance %(VO2peak) at TLAC (P=0.85) and OBLA (P=0.71) compared to a placebo treatment. Whilst VE supplementation did not enhance performance it did not impair performance compared to a placebo. Training significantly enhanced velocity at TLAC (P=0.00) and OBLA (P=0.05). No training-induced improvements in %VO2peak at TLAC (P=0.06) and OBLA (P=0.40) were observed. CONCLUSION: Daily VE supplementation for 35 days does not enhance or impair physiological performance at fixed blood lactate concentrations. Long-term VE supplementation for the purposes of performance enhancement is not recommended.